2022
DOI: 10.1007/s40415-022-00793-5
|View full text |Cite
|
Sign up to set email alerts
|

Neotropical Anacardiaceae (cashew family)

Abstract: Anacardiaceae is an ecologically and economically important plant family of about 200 species in 32 genera in the Neotropics. The family is particularly diverse in leaf architecture and fruit morphology, making it a model family to study the evolution of structural diversity as it correlates with lineage diversification. This fruit diversity is the primary reason 11 of the Neotropical genera are monotypic and that so many genera are recognized in the Anacardiaceae. The economic value of the family is driven by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 196 publications
0
10
0
Order By: Relevance
“…Consequently, inter and intra-specific relations in the family were confirmed through combined molecular and/or morphological analyses by specialists (Pell 2004;Wannan 2006;Silva-Luz et al 2019;Bordignon & Vogel 2020). It includes 81 genera and 800 species, distributed mainly in tropical and subtropical regions, but also extends to temperate regions, in diverse dry and humid habitats, mostly low lands (Pell 2009;Pell et al 2011;Silva-Luz 2011;Silva-Luz et al 2021;Mitchell et al 2022). The highest diversity within the family is located in the tropics and its center of origin is Southeast Asia, with Paleotropical regions being richer than Neotropical ones, with ca.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…Consequently, inter and intra-specific relations in the family were confirmed through combined molecular and/or morphological analyses by specialists (Pell 2004;Wannan 2006;Silva-Luz et al 2019;Bordignon & Vogel 2020). It includes 81 genera and 800 species, distributed mainly in tropical and subtropical regions, but also extends to temperate regions, in diverse dry and humid habitats, mostly low lands (Pell 2009;Pell et al 2011;Silva-Luz 2011;Silva-Luz et al 2021;Mitchell et al 2022). The highest diversity within the family is located in the tropics and its center of origin is Southeast Asia, with Paleotropical regions being richer than Neotropical ones, with ca.…”
Section: Introductionmentioning
confidence: 97%
“…Anacardiaceae species stand out due to the economic significance of their edible fruits such as mango Mangifera indica L., cashew nut Anacardium occidentale L., rose pepper Schinus L. and mombins Spondias L., their beverages, good quality timber, medicinal properties, ornamentals, and the industrial employment of their resins and tannins (Font Quer 1964;Judd et al 2009;Muñoz 2000;Pell 2009;Pell et al 2011;Simpson 2006;Stevens 2023;Souza & Lorenzi 2019;Silva-Luz et al 2021;Mitchell et al 2022). Many species are used in reforestation and ecological restoration planning due to their pioneer character, as well Rodriguésia 75: e01372022.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A close relationship of Burseraceae and Anacardiaceae is well-established, with both families previously included in the family Terebinthaceae and sharing the synapomorphies of vertical intercellular secretory canals in the primary and secondary phloem and the ability to synthesise biflavonyls ( Wannan et al., 1985 ; Wannan, 1986 ; Wannan and Quinn, 1990 ; Wannan and Quinn, 1991 ; Terrazas, 1994 ). More recent molecular studies support Anacardiaceae and Burseraceae as monophyletic, although infra-familial classifications are in need of revision ( Gadek et al., 1996 ; Pell, 2004 ; Weeks et al., 2014 ; Muellner-Riehl et al., 2016 ; Mitchell et al., 2022 ). Morphological studies have shown a close affinity in floral structure of members of the monogeneric family Kirkiaceae to Anacardiaceae and Burseraceae ( Bachelier and Endress, 2008 ), and, together, these families form a moderately to well-supported clade in recent molecular studies ( Muellner et al., 2007 ; Muellner-Riehl et al., 2016 ; Li et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%